Association between serum folate concentrations and all-cause mortality in U.S. adults: a cohort study based on National Health and Nutrition Examination Survey III - Zhao, Qingya; Lv, Xiaogang; Liu, Qi; Hu, Zhao; Zhan, Yiqiang (Frontiers in Nutrition, 2024)
The association between serum folate and all-cause mortality in general population remains unclear. The objective of this study was to investigate the potential association between serum folate concentrations and all-cause mortality in a large, prospective, long-term U.S. cohort. Our study included adults from the National Health and Nutrition Examination Survey (NHANES) III, and mortality data was obtained by linking with the National Death Index (NDI) until December 31, 2019. Cox proportional hazard models were used to calculate hazard ratios (HR) and 95% confidence intervals (CI) to assess the association between serum folate concentrations and all-cause mortality. A total of 12,862 participants were included in this cohort study. After a median follow-up of 26.4 years [interquartile range (IQR), 15.4-28.7 years], a total of 5,299 deaths were recorded. The risk of death was lower by 12% per 1.0 g/L increase in log-transformed serum folate concentrations (HR, 0.88; 95% CI, 0.83-0.94). Compared with the lowest quartiles of serum folate level, the risk of death was lower in the second (HR, 0.84; 95% CI, 0.72-0.97), third (HR, 0.78; 95% CI, 0.68-0.91) and the highest quartiles (HR, 0.78; 95% CI, 0.69-0.88) in multivariable-adjusted model. In subgroup analyses, the inverse association between serum folate and all-cause mortality remained statistically significant for women, men and non-Hispanic whites. Higher serum folate levels were found to be significantly associated with reduced risk of all-cause mortality. However, further studies are needed to verify these findings and explore the underlying mechanism.